Formy organizacji pracy uczniów w procesie edukacji inkluzyjnej - Twardowski, Andrzej (Rocznik Pedagogiczny, 2019)
In recent years, increasing attention has been devoted to developing pedagogical approaches that are appropriate in heterogeneous classrooms. Teachers working in inclusive classrooms must develop forms of student work that do not isolate and stigmatize learners with special educational needs. In the first part of the article, the author analyzes the origin and essence of the idea of inclusive edu- cation. In the second part of the article, three forms of work organization for students in inclusion classes are characterized: Peer Tutoring, Cooperative Learning and Multi-level Teaching.